Dengue Virus and Vaccines: How Can DNA Immunization Contribute to This Challenge? - Alves, Ada Maria Barcelos; Costa, Simone Morais; Pinto, Paolla Beatriz Almeida (Frontiers in Medical Technology, 2021)
Dengue infections still have a tremendous impact on public health systems in most countries in tropical and subtropical regions. The disease is systemic and dynamic with broad range of manifestations, varying from mild symptoms to severe dengue (Dengue Hemorrhagic Fever and Dengue Shock Syndrome). The only licensed tetravalent dengue vaccine, Dengvaxia, is a chimeric yellow fever virus with prM and E genes from the different dengue serotypes. However, recent results indicated that seronegative individuals became more susceptible to develop severe dengue when infected after vaccination, and now WHO recommends vaccination only to dengue seropositive people. One possibility to explain these data is the lack of robust T-cell responses and antibody-dependent enhancement of virus replication in vaccinated people. On the other hand, DNA vaccines are excellent inducers of T-cell responses in experimental animals and it can also elicit antibody production. Clinical trials with DNA vaccines have improved and shown promising results regarding the use of this approach for human vaccination. Therefore, in this paper we review preclinical and clinical tests with DNA vaccines against the dengue virus. Most of the studies are based on the E protein since this antigen is the main target for neutralizing antibody production. Yet, there are other reports with DNA vaccines based on non-structural dengue proteins with protective results, as well. Combining structural and non-structural genes may be a solution for inducing immune responses aging in different infection moments. Furthermore, DNA immunizations are also a very good approach in combining strategies for vaccines against dengue, in heterologous prime/boost regimen or even administering different vaccines at the same time, in order to induce efficient humoral and cellular immune responses.